Learning to teach small classes : lessons from East Asia - Maurice, Galton; Lai, Kwok Chan; Chan, Kam Wing (Routledge, 2015)
"The justification for smaller classes has traditionally been that students can receive more individual attention and be provided with a curriculum that promotes student centred learning. However, in Asia where student engagement is generally over 90% in primary school classrooms, the focus of smaller classes is for teachers to increase the quality of their teaching, building on the already impressive levels of student engagement. Learning to Teach Small Classes comprehensively instructs teachers on ways they can utilise the advantage of a smaller class to its fullest potential. It works through different case studies and gives examples of successful classroom practice in each of the core subject areas (Chinese, English and Mathematics). Chapters include: - Setting Objectives, Asking and Answering Questions - Sustaining Successful Group and Pair Work - The Use of Feedback and Assessment for Developing Independence in Learning - Bringing it all together and Sustaining Effective Practice With questions for discussion and further suggested reading, this book is a invaluable resource for anyone involved in East Asian teaching and education policy"--